1982
DOI: 10.1080/01483918208066908
|View full text |Cite
|
Sign up to set email alerts
|

Metal Cation/Anion Speciation via Paired-Ion, Reversed Phase HPLC with Refractive Index and/or Inductively Coupled Plasma Emission Spectroscopic Detection Methods

Abstract: Conventional high performance 1 i qu i d chromatography instrumentation and packing materials can be inexpensively and rapidly utilized for the qualitative and quantitative analysis of various metal cations or anions. The final approaches utilize reversed phase HPLC in the form of paired-ion separations. The detection of individually eluted, fully resolved metal cations or anions is possible conventional refractive index or inductively coupled plasma emission spectroscopic detection. In many cases, unresolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Additional experiments were performed using varying concentrations of methEmol in the mobile phase and various LC flow rates; It was found that increasing the flow rate from 1.5 to 2.1 mL min"1 and increasing the methEmol concentration from 5 to 10% reduced the retention times in Table V substantially: doubly charged ions now eluted at about 8 min. This is similar to behavior reported by others (9).…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Additional experiments were performed using varying concentrations of methEmol in the mobile phase and various LC flow rates; It was found that increasing the flow rate from 1.5 to 2.1 mL min"1 and increasing the methEmol concentration from 5 to 10% reduced the retention times in Table V substantially: doubly charged ions now eluted at about 8 min. This is similar to behavior reported by others (9).…”
Section: Methodssupporting
confidence: 93%
“…However, most measurement techniques for trace elemental analysis are suitable for determining only the total amount of individual elements and do not provide information 1 Present address: Department of Chemistry, Ball State University, Muncie, IN 47306. about the chemical states present. Initial investigation of techniques for "elemental speciation" began in the early 1970s (3,4), and research activity in this area has escalated steadily since then (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile-phase ion chromatography can be used to determine total gold as well as Au(CN) 2 and Au(CN) 4 - [34][35][36]. Bushee, Krull and coworkers described an ionpairing reverse-phase method for the separation of Cu(I) and Cu(II) [38]. Lead speciation of Et 3 Pb + and Me 3 Pb + along with some other organometallic species was reported by MacCrehan et al [32].…”
Section: Mercurymentioning
confidence: 99%
“…Several other papers concerned with FI-ICP or FI-ICP-MS also exist [88][89][90][91][92][93][94][95], however many were performed offline [93][94].…”
Section: Analysis By Icp-ms/96mentioning
confidence: 99%